THE ANALYSIS OF THE USAGE OF INTERNET LANGUAGE FEATURES USED BY MEN AND WOMEN ON SOCIAL MEDIA - Gunawan Tambunsaribu; Teguh Prasetyo (Prodi Sastra Inggris UKI, 2024)
The rapid advancement of computers and the internet has led to the emergence of internet language as a prominent linguistic phenomenon. Exploring the distinctive features of this language has become an important area of study in recent years. This research analyzes the typical features of internet language used by men and women commenters on Instagram, with a particular emphasis on gender-based differences. The study investigates ten common digital language features: multiple punctuation marks, unconventional spelling, capitalization, asterisks for emphasis, written-out laughter, music/noise references, action descriptions, emoticons, abbreviations, and rebus writing. These features serve as the basis for data analysis. A qualitative approach is used to examine the collected data in-depth. The findings reveal that while both genders use capital letters (though not in all caps) and multiple punctuation marks (such as exclamation points and periods), women employ more internet language features overall—42 features compared to 31 by men. Additionally, woman users are more likely to extend consonants in their spelling, whereas men tend to repeat vowels. These differences illustrate how users modify language for efficiency and self-expression in digital communication.